The Effects of Health on the Settlement Intention of Rural–Urban Migrants: Evidence from Eight Chinese Cities - Huang, Xu; He, Dongsheng; Liu, Ye; Xie, Shenghua; Wang, Ruoyu; Shi, Zhilei (Applied spatial analysis and policy, 2021)
The growing number of rural–urban migrants in China has made it important to understand the factors contributing to this migration. By using data from a nationally representative survey and multilevel logistic regression, this study examines the extent to which the health of rural–urban migrants influences their settlement intention in the cities chosen as their destinations. It goes beyond past studies by disentangling the complexity of settlement intention into short- and long-term decisions, and by examining the moderating role of social support provided by the host society. The results of regression analysis revealed that physical and mental health play a crucial role in shaping the settlement intention of migrants, but their effects are not always identical in cases of short- and long-term intentions. Migrants consider their mental rather than physical health when reporting short-term settlement intention, and assign greater importance to physical health than mental health when indicating long-term settlement intention. Furthermore, the relationship between migrants’ health and their settlement intention is moderated by social support from local residents and the local neighbourhood. These results highlight the importance of reducing health inequality across social groups to allow for inclusive urbanization in China.